Innovation in the Development of Learning Animation Videos Through the Powtoon App in the Learning Design Course - Abdul Hamid K; Marlan; Adi Widarma (Postgraduate, University of Mataram, 2025)
The learning process for the Learning Design course in the Unimed Building Engineering Education Department (JPTB) has so far only been carried out with a presentation or lecture strategy, where students are more passive and only act as good listeners so that the expected learning objectives and competencies are not achieved. In addition, the implementation of the KKNI-based Merdeka Learning Campus (MBKM) based curriculum requires students to produce learning products. Therefore, to improve students' abilities in Learning Design learning, it is always necessary to change or innovate continuously so that they can achieve the learning objectives that have been set determined, one of which is the ability to develop Video Animation which is not only influenced by the learning model but also the application used. The proposed research aims to produce Learning Video Animations to improve student competence. Advances in information and communication technology have made learning animation videos visible using the Powton application learning can contain the same information as printed textbooks and can insert teaching materials not only in text form, it can be in the form of animation, audio or video and can be stored on CDs, flash discs, computers and smartphones so it doesn't take up a lot of space and carry it more easily, easier than a textbook. On the basis of the above, research will be carried out on the innovation of developing Powton animation videos in the Learning Design course with the aim of knowing the Feasibility of Learning Animation Videos using the Powtoon Application in the Learning Design course. How is Student Response to Learning Animation Videos using the Powtoon Application in the Learning Design course. The learning device development model used in this study is the 4-D Thiagarajan model (1974). This development model consists of 4 stages of development, namely: Define; Design, Develop, and Disseminate. Feasibility of Video Animation is done by asking for expert reviews. Materials, learning media experts and learning design experts. The effectiveness of using the Powton application is from the results of the pretest and post test results of student learning taking the learning design course. The expected results or outputs of this study are: produce learning, animation teaching material products using applications that can be applied to improve students' abilities in learning design materials; and produce scientific publications, both in the form of Seminar Proceedings and international journals about the use of teaching materials to improve skills in the Learning Design course.